Niobium – plausiblity for use in restorative dentistry - A, Meenakshi; C, Sabarigirinathan; V.P, kiruthiga (Journal of Oral and Dental Sciences, 2018)
Rare earth elements have gained enormous popularity in the recent years because of their excellent mechanical properties along with their inertness, which easily makes them biocompatible in the oral environment. Niobium is in use in the biomedical field in small proportions with other primary elements but not as principal constituent. In this review the credibility of the element Niobium as a restorative material its advantages over others currently in use in dentistry is explained by reviewing the literature. This paper also reviews about the castability and biocompatibility of niobium (Nb) in detail.
Keywords: Niobium; Casting; Grain Refining; Corrosion Resistance; HSLA (High-Strength Low Alloyed Steel)